Antifungal Investigation of the Constituents of Moringa oleifera lamk. Root Bark Extract. - JHA, NIDHI; Mohanka, Reena; AZAD, RANI (Asian Journal of Chemistry, 2010)
Antifungal activity of Moringa oleifera root bark extract was treated against Aspergillus niger and Neurospora crassa. Percent mycelial inhibition of aqueous, methanolic and ethanolic extract were determined. Significant inhibition especially of ethanolic extract was seen against Neurospora. Comparatively the extracts were less inhibitory against Aspergillus sps.